Reimplantation of the upper lobe bronchus after lower sleeve lobectomy or bilobectomy: long-term results. (17th January 2018) - Maurizi, Giulio; Ciccone, Anna Maria; Vanni, Camilla; D'Andrilli, Antonio; Ibrahim, Mohsen; Andreetti, Claudio; Menna, Cecilia; Tierno, Simone M; Venuta, Federico; Rendina, Erino A
Abstract: OBJECTIVES: The advantages of a bronchial sleeve resection are well established. A clear majority of reported cases are of upper lobe sleeve resection. Reimplantation of the upper lobe bronchus after a lower sleeve lobectomy or bilobectomy (the so-called Y-sleeve resection) is infrequent. Related technical peculiarities are the main issues. We present our experience and results in this setting. METHODS: Between 1989 and 2015, we performed 28 Y-sleeve resections of the left lower lobe ( n  = 18) or right middle and lower lobes ( n  = 10). The lung-sparing reconstructive operation was performed for non-small-cell lung cancer in 23 cases, for bronchial carcinoid tumour in 4 cases and for a cystic adenoid carcinoma in 1 case. Anastomotic reconstruction was performed by interrupted 4-0 absorbable sutures (monofilament material). RESULTS: All the resections were complete (R0). Postoperative mortality was 3.6%. The rate of major complications was 10.7% (1 myocardial infarction, 1 anastomotic stenosis requiring dilatation and 1 anastomotic fistula). Among the 23 patients with non-small-cell lung cancer (18 men and 5 women; mean age 58 ± 12 years), 8 were Stage I, 9 were Stage II and 6 were Stage IIIa. At a mean follow-up of 46 months, the recurrence rate was 32%. There were 2 loco-regional recurrences. No endobronchial or perianastomotic recurrence occurred. The 3- and 5-year overall and disease-free survival rates of patients with non-small-cell lung cancer were 76.3% and 55.1% and 68.7% and 62.9%, respectively. CONCLUSIONS: A Y-sleeve resection with reimplantation of the upper load bronchus is a technically feasible and oncologically adequate operation.